The role of Type III secretion system in the pathogenesis of Pseudomonas aeruginosa microbial keratitis - Justin J Yang; Kai-Si Claire Tsuei; Elizabeth P Shen (Tzu Chi Medical Journal)
Pseudomonas aeruginosa is the most commonly isolated Gram-negative pathogen causing sight-threatening microbial keratitis (MK). Contact lens wear is the most significant risk factor associated with pseudomonal MK. Understanding the pathogenesis of MK due to P. aeruginosa and its interactions with contact lenses is crucial in preventing these often rapidly progressive and highly antibiotic-resistant infections. Bacterial virulence factor Type III secretion system (T3SS) has significant interplays between contact lens material, antibiotic sensitivity, disinfectant selectivity, and bacterial cell invasion. Depending on the T3SS exotoxins produced, P. aeruginosa strains are divided into cytotoxic or invasive strains. Cytotoxic strains are relatively resistant to commercial disinfectants, while invasive strains are more antibiotic resistant. Therefore, contact lens wearers are more predisposed to cytotoxic P. aeruginosa infections, and patients with trauma or previous surgery are more prone to infection by invasive strains. Previous studies with mutant P. aeruginosa strains unable to produce T3SS exotoxins were more susceptible to disinfectants and less able to adhere to soft contact lenses, indicating an essential role of T3SS in bacterial virulence. Invasion of P. aeruginosa intracellularly was found to be associated with control of scaffold protein IQ-domain GTPase-activating protein 1 (IQGAP1) and human corneal epithelial cell tight junctions. Knockdown of IQGAP1 strengthened tight junctions that prevented intracellular survival of invasive P. aeruginosa strains and enhanced corneal epithelial cell survival. These novel findings of the vital role of T3SS in the pathogenesis of pseudomonal MKs will provide new guidelines in both prevention and treatment of this common eye-blinding infection.